Experiences of newly qualified Canadian social worker - Newberry-Koroluk, Andrea (My University, 2011)
The article focuses on the experiences of newly qualified social workers in order to develop recommendations for social work educators, researchers, employers, and new social workers. It mentions that the social workers includes several social work methods including micro skills such as interviewing, giving feedback, and working with hostile clients.
Keywords: social workers; educators; employees; public welfare; interviewing